Mitochondria Export Sulfur Species Required for Cytosolic tRNA Thiolation. Issue 6 (21st June 2018) - Pandey, Alok; Pain, Jayashree; Dziuba, Nathaniel; Pandey, Ashutosh K.; Dancis, Andrew; Lindahl, Paul A.; Pain, Debkumar
Summary: In eukaryotes, mitochondria have been hypothesized to generate sulfur species required for tRNA thiolation in the cytosol, although no direct evidence thus far exists. Here we have detected these sulfur species, making use of our observation that isolated yeast cytosol alone is unable to thiolate tRNAs but can do so upon addition of mitochondria. Mitochondria were found to utilize the cysteine desulfurase Nfs1 to produce sulfur-containing species with masses ranging from 700 to 1, 100 Da. Mitochondria exported these species via the Atm1 transporter in the inner membrane. Once exported to the cytosol, these sulfur species promoted cytosolic tRNA thiolation with no further requirement of mitochondria. Furthermore, we found that the Isu1/2 scaffolds but not the Ssq1 chaperone of the mitochondrial iron-sulfur cluster machinery were required for cytosolic tRNA thiolation, and thus the sulfur utilization pathway bifurcates at the Isu1/2 site for intra-organellar use in mitochondria or export to the cytosol. Graphical Abstract: Highlights: Mitochondria generate activated sulfur species (Sint ) with masses from 700 to 1, 100 Da Sint synthesis requires Nfs1 and Isu1/2, but not Ssq1, of the Fe-S cluster machinery Mitochondria export Sint to the cytosol via the ABC transporter, Atm1 Cytosol uses exported Sint for thiolation of tRNAs specific for Lys, Glu, and Gln Abstract : Critical signals and metabolites move between mitochondria and cytosol, and such communications are essential for cellular homeostasis. Pandey et al. demonstrate that mitochondria generate activated sulfur intermediates (Sint ). The intermediates are exported to the cytosol in an ATP-dependent fashion, and there they are utilized for thio-modification of tRNAs.